Analisis Sistem Informasi Akuntansi Atas Pembayaran Dana Pensiun Pada PT TASPEN (Persero) Kantor Cabang Makassar - Ridha, Akhmad; Tikollah, M. Ridwan; Hamzah, Hajrah (STIEM BONGAYA, 2025)
This study aims to analyze the Accounting Information System for Pension Fund Payments at PT Taspen (Persero) Makassar Branch Office. The variable in this study is the Accounting Information System as a single variable. The subject and focus of this study are to use subjects related to the Accounting Information System at PT Taspen (Persero) Makassar Branch Office, namely all documents related to pension fund payments. Data collection was carried out using documentation techniques. Data analysis was carried out using qualitative descriptive methods in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the components of the Accounting Information System consisting of personnel, procedures, data, software, hardware and internal control have complied with the standards set at PT Taspen (Persero) Makassar Branch Office and based on Romney and Stainbart's theory, these components have met the existing criteria.